Low-dose naltrexone as a treatment for vulvodynia: A case series - Renee T. Sullender; R. Gina Silverstein; Diamond M. Goodwin; Asha B. McClurg; Erin T. Carey (Case Reports in Women's Health)
Vulvodynia is a chronic vulvar pain condition that can be challenging to treat and often requires multi-modal interventions for symptom management. Low-dose naltrexone (LDN) is a reversible competitive antagonist at opioid receptors and may have utility in treating chronic pain conditions. In a specialty gynecology clinic at an academic medical center, patients with poorly controlled vulvodynia who had failed standard treatments were offered LDN as an adjunct pain treatment. This case series describes the experience of three patients with chronic vulvodynia who added LDN to their treatment regimen. All patients reported subjective improvement in their symptoms without side-effects. Additional research is needed on the efficacy of LDN for chronic pelvic pain conditions such as vulvodynia as well as the long-term safety profile of such use.